Conduction velocity mapping in Bachmann Bundle using Omnipolar Technology. (19th May 2022) - Volpato, G; Casella, M; Compagnucci, P; Valeri, Y; Parisi, Q; Cipolletta, L; Carboni, L; Bondavalli, B; La Piscopia, V; Messano, L; Ricciotti, J; Guerra, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Bachmann's bundle is emerging as a critical component of atrial fibrillation (AF) catheter ablation (CA). The introduction of Omnipolar Technology (OT) in the new Ensite X Cardiac Mapping system, provides three-dimensional information on conduction velocity, activation direction and voltage of endocardial potentials, independently of catheter orientation. OT can create a wave speed map: a color map type coded by numeric value of conduction velocity. Objective: To assess the feasibility and reliability of left atrium wave speed maps in Bachmann's bundle identification and conduction velocity characterization. Methods: We included 10 patients, (60% male, 40% female, mean age 56±8.7 years) undergoing CA for paroxysmal AF at our institution with new Ensite X Cardiac Mapping System; the left atrium (LA) was mapped with the Advisor HD Grid catheter. A sinus rhythm voltage map and wave speed map were obtained and analyzed to identify high conduction velocity areas throughout the Bachmann's bundle location (septum, roof and left atrium appendage (LAA)). Results: Wave speed mapping allowed the identification, at the septum, roof and LAA, of a myocardial bundle with greater speed values (2.5±0.3 m/s) with respect to mean atrial value (1±0.1). Pulmonary vein antra conduction velocity mean value was 1.2±0.4 m/s. Standard voltage map (low-voltage areas defined as any LA region with voltage values < 0.5 mV) was compared with wave speed map. Standard voltage map (Figure 1) did not discriminate Bachmann's bundle, while wave speed map did (Figure 2). Conclusion: Wave speed mapping introduced by OT is a promising new map type, allowing characterization and identification of Bachmann's bundle. Further studies are needed to assess the impact of this new technology on procedural workflow and clinical outcome.